Balancing patient priorities for technical and interactional aspects of care in a measure of primary care quality - Mulder, Carol (Prim Health Care Res Dev, 2019)
AIM: This study attempts to strike a balance to measure primary care quality in a way that considers what is important to patients, providers and the healthcare system, all at the same time. BACKGROUND: The interest in delivering patient-centered primary care implies a need for patient-centered performance measurement. However, the distinction between measures of patient experience and technical aspects of care raises an unanswerable question: if a provider has good performance on technical measures but not on patient experience measures (or vice versa), what can be said about the quality of care? METHODS: We surveyed patients to determine the relative priorities of each of a series of primary care measures in the patients’ relationship with their primary care provider. The on-line survey was co-designed with patient co-investigators. The items consisted of 14 primary care quality measures used in pre-existing performance report, 41 additional indicators including a novel set of patient-generated Key Performance Indicators and 17 questions about patients’ demographics, health and socioeconomic status as well as open-ended questions. FINDINGS: Despite challenges, the study suggests that this is feasible. We argue that it is necessary to get better at measuring and finding ever-better ways to put patients at the center of primary care